Evaluating a complex research capacity-building intervention: Reflections on an evaluation of the African Institutions Initiative. (January 2017) - Marjanovic, Sonja; Cochrane, Gavin; Robin, Enora; Sewankambo, Nelson; Ezeh, Alex; Nyirenda, Moffat; Bonfoh, Bassirou; Rweyemamu, Mark; Chataway, Joanna
There is increasing policy demand for real-time evaluations of research and capacity-building programmes reflecting a recognition of the management, governance and impact gains that can result. However, the evidence base on how to successfully implement real-time evaluations of complex interventions in international development efforts is scarce. There is therefore a need for reflective work that considers methodologies in context. This article shares learning from the experience of conducting a participatory, real-time, 'theory driven' evaluation of the African Institutions Initiative, a Wellcome Trust-funded programme that aimed to build sustainable health research capacity in Africa at institutional and network levels, across seven research consortia. We reflect on the key challenges experienced and ways of managing them, highlight opportunities and critical success factors associated with this evaluation approach, compared with alternative evaluation approaches.